Performance Analysis of OLSR Routing Protocol for Video Streaming Over Mobile Ad Hoc Networks. : تقييم أداء بروتوكول توجيه حالة الربط المحسن في إرسال الفيديو عبر الشبكات المتنقلة المخصصة لهدف معين - Hanadi Yahya Darwisho (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2019)
In view of the increasing use of mobile devices in addition to the high demand for the applications provided by these devices including video streaming, most companies have tended to pay attention to the mobile ad hoc networks and search for solutions to the problems and obstacles that hindered the process of sending video in this type of networks. One of the solutions discussed: Solutions at the level of video compression technology where many of the standards that were used in the process of video encoding and that provide good video quality by using a few bits in the coding process as provided us with acceptable bandwidth for the user and are flexible in handling with errors. These standards are: "H. 264/ MPEG-4 part 10". There was also a solution at the level of routing during the transmission of video in real time over the mobile ad hoc networks so in this paper has been studied OLSR routing protocol that support the transmission of video on the basis of delay, network load and throughput and evaluated the performance by changing the model where the node is located (Node Placement Model) in a large network and in a small network as well as for different video resolutions.
Keywords: الشبكات المتنقلة المخصصة، بروتوكول التوجيه، بروتوكول حالة الربط المحسن، الفيديو، النموذج الذي تتوضع فيه العقدة.